A photostable monomeric superfolder green fluorescent protein. (16th June 2020) - Valbuena, Fernando M.; Fitzgerald, Ivy; Strack, Rita L.; Andruska, Neal; Smith, Luke; Glick, Benjamin S.
Abstract: The green fluorescent protein (GFP) from Aequorea victoria has been engineered extensively in the past to generate variants suitable for protein tagging. Early efforts produced the enhanced variant EGFP and its monomeric derivative mEGFP, which have useful photophysical properties, as well as superfolder GFP, which folds efficiently under adverse conditions. We previously generated msGFP, a monomeric superfolder derivative of EGFP. Unfortunately, compared to EGFP, msGFP and other superfolder GFP variants show faster photobleaching. We now describe msGFP2, which retains monomeric superfolder properties while being as photostable as EGFP. msGFP2 contains modified N‐ and C‐terminal peptides that are expected to reduce nonspecific interactions. Compared to EGFP and mEGFP, msGFP2 is less prone to disturbing the functions of certain partner proteins. For general‐purpose protein tagging, msGFP2 may be the best available derivative of A. victoria GFP. Abstract : Superfolder green fluorescent protein (GFP) variants are suitable for imaging in challenging cellular environments, but they suffer from rapid photobleaching. Here, we describe a photostable monomeric superfolder GFP called msGFP2. In addition to its enhanced photophysical properties, msGFP2 contains N‐ and C‐terminal peptides derived from an mCherry variant that has reduced cytotoxicity. These improved fluorescent proteins should be of general utility.